A medida socioeducativa de internação: tensão entre o caráter educativo e o punitivo - Borges, Keilla Ellen (2014)
The present work aims to confront the theoretical reality of the social-educational measure of detention applied to adolescents when in conflict with the law, with the practical reality, which has not distanced itself from the primitive models of penalty application. That proposal ultimately demonstrates a tension between the educational character praised by the Child and Adolescent Statute and the punitive character, materialized in fulfilment with those measures. On a broader understanding scale, the problem points at the crisis of legitimacy of human rights, criticized for been presented as ideals of difficult operationalization and accomplishment, even for countries that intend to adopt its precepts